Challenges Conducting Research with Adolescents in Public Schools. Issue 1 (18th October 2018) - Bonnell, Kory J.; Hargiss, Christina L. M.; Norland, Jack E.
Abstract : Core Ideas: To research adolescents, permission needs to be gained from multiple gatekeepers. More gatekeepers exist in larger school districts and areas with greater populations. Access to student populations becomes increasingly more difficult and less likely with more gatekeepers. Higher participation rates occur in rural schools than in urban cluster and large metropolitan/inner city areas. Gatekeepers are a necessary safeguard, but will limit research opportunities. Understanding the knowledge and perceptions of adolescents is an integral part of creating better curriculum and education materials in the natural sciences. This study explores the challenges of working with a protected population in a public school setting in terms of Institutional Review Board standards, the complex process of a researcher gaining access to the public schools, and the difficulty in attaining both parental and youth consent. In total 39 school districts throughout the state of Minnesota, USA, were invited to participate in the study; school districts were contacted from three demographics including (1) large metropolitan/inner city, (2) urban cluster, and (3) rural. Overall, securing participation among all demographics was challenging, though rural populations were the easiest when compared with the other demographics. Differences between groups were related to how gatekeepers granted approval. More gatekeepers exist in larger school districts and areas with greater populations. The ongoing complexities of gaining access to adolescents in public school settings may cause problems in determining what students actually know about the natural sciences and could hinder creation of appropriate education materials based on this information. The information in this study can be used by researchers, extension professionals, and educators to better understand how to navigate the current challenges that exist when researching a protected population in public schools.